Pain expectations, experiences and coping strategies used by post-operative patients: A descriptive phenomenological study - Richard Sakyi; Edward Appiah Boateng; Abigail Kusi-Amponsah Diji; Kenneth Adjei Afful; Vincent Afriyie Nimoh; Philomena Asakeboba Ajanaba; Mabel Dorothy Adjei; Felix Apiribu; Veronica Millicent Dzomeku (PLoS ONE, 2025)
Objectives Post-operative pain(POP) is still an unresolved problem worldwide, including in limited-resource countries such as Ghana. Earlier studies have mainly focused on postoperative pain experiences of patient with little attention to their pain expectations and coping strategies. The current study sought to qualitatively explore pain expectations, pain experiences, and coping strategies used by adult surgical patients to help add patients’ perspectives to surgical pain management. Methods A descriptive phenomenological design approach was used to study nine purposively sampled surgical patients receiving care at a regional hospital in Ghana. Participants were individually interviewed before and during the postoperative period to share their opinions on their pain expectations, postoperative pain experiences, and coping strategies. Recruitment and data collection took place between July 8, 2021, and August 30, 2021. The semi-structured individual interviews were audio-recorded, transcribed verbatim, and content analysed to generate themes that described participants’ accounts. Results The participants consisted of six females and three males, aged 24–40, who had undergone major surgeries. This study derived three main themes: diverse pain expectations and experiences, post-operative pain effects, and post-operative pain coping strategies. The study revealed that participants had different pain expectations and experiences, and surgical pain affected their activities of daily living and emotions. Participants coped with the postoperative pain by using personal strategies and seeking support from nurses. Conclusion Pain expectation of surgical patients affects their post-operative pain experiences. Surgical patients use coping strategies in their post-operative pain management. More needs to be done in reducing surgical patients’ experience of post-operative pain.